Combined therapy with sitagliptin plus granulocyte-colony stimulating factor in patients with acute myocardial infarction — Long-term results of the SITAGRAMI trial. (15th July 2016) - Gross, Lisa; Theiss, Hans Diogenes; Grabmaier, Ulrich; Adrion, Christine; Mansmann, Ulrich; Sohn, Hae-Young; Hoffmann, Ellen; Steinbeck, Gerhard; Franz, Wolfgang-Michael; Brenner, Christoph
Abstract: Background: Autologous progenitor cell therapy comprising granulocyte-colony stimulating factor (G-CSF) for mobilization of bone-marrow derived progenitor cells (BMPCs) into peripheral blood and inhibition of dipeptidylpeptidase-IV by sitagliptin for enhanced myocardial recruitment of circulating BMPCs has been shown to improve survival after acute myocardial infarction (MI) in preclinical studies. In the SITAGRAMI trial we found that during short-term follow-up G-CSF plus sitagliptin (GS) failed to show a beneficial effect on cardiac function and clinical events in patients with acute MI that underwent successful PCI. The objective of the present analysis was to assess the impact of GS versus placebo treatment on long-term clinical outcomes of the SITAGRAMI trial patient population. Methods: In the randomized, prospective, double-blind, placebo-controlled SITAGRAMI trial, 174 patients with acute MI were assigned to GS or placebo in a 1:1 ratio. The primary outcome for the present long-term analysis was the composite of death, MI or stroke on long-term follow-up. Results: The median [IQR] follow-up duration was 4.50 [3.56–5.95] years. The primary outcome occurred in 12.8% of patients assigned to placebo and 9.2% assigned to GS (HR 0.69, 95% CI 0.28–1.69; p = 0.42). The incidence of the combined cardiovascular outcome was 47.7% in the placebo- and 41.4% in the GS-group (HR 0.75, 95% CI 0.48–1.18; p = 0.21). Overall, there was no significant difference in MACCE rates between both treatment groups (p = 0.41). Conclusion: These long-term follow-up data indicate that GS therapy does not improve clinical outcomes of patients with acute MI.